2011
DOI: 10.1038/hr.2011.195
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effects and mechanisms of chlorogenic acids

Abstract: Chlorogenic acids (CGAs) are potent antioxidants found in certain foods and drinks, most notably in coffee. In recent years, basic and clinical investigations have implied that the consumption of chlorogenic acid can have an anti-hypertension effect. Mechanistically, the metabolites of CGAs attenuate oxidative stress (reactive oxygen species), which leads to the benefit of blood-pressure reduction through improved endothelial function and nitric oxide bioavailability in the arterial vasculature. This review ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
172
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(183 citation statements)
references
References 65 publications
(108 reference statements)
2
172
1
8
Order By: Relevance
“…Both acute and chronic administration of 5-CQA showed almost identical results on SBP as seen in GCE administration on MS animal model diet induced. Furthermore, several mechanisms of SBP reduction by CGA and it metabolites such as, inhibition of nicotinamide adenine dinucleotide phosphate oxidase expression and activity, reduced free radical production, directly scavenging free radicals, stimulation of NO production by the endothelial-dependent pathway, and inhibition of angiotensin-converting enzyme in the plasma [35]. Hypotension effect of GCE could be influenced by roasting condition which that increase antioxidant activity [36].…”
Section: Lukitasari Et Almentioning
confidence: 99%
“…Both acute and chronic administration of 5-CQA showed almost identical results on SBP as seen in GCE administration on MS animal model diet induced. Furthermore, several mechanisms of SBP reduction by CGA and it metabolites such as, inhibition of nicotinamide adenine dinucleotide phosphate oxidase expression and activity, reduced free radical production, directly scavenging free radicals, stimulation of NO production by the endothelial-dependent pathway, and inhibition of angiotensin-converting enzyme in the plasma [35]. Hypotension effect of GCE could be influenced by roasting condition which that increase antioxidant activity [36].…”
Section: Lukitasari Et Almentioning
confidence: 99%
“…Among 3 available studies on this topic, 2 studies reported a protective effect of 1 cup of boiled 8 or filtered coffee 9 on LDL oxidation, whereas 1 study found neither short-term nor long-term effects of filtered coffee consumption on lipid peroxidation. 10 As opposed to caffeine, CGA have been demonstrated to have antihypertensive effects, 11,12 possibly via nitric oxide-mediated vasodilation. 12 Results from an RCT of 23 healthy adults showed that CGA ingestion significantly reduced systolic blood pressure by 2.41 mm Hg and diastolic blood pressure by 1.53 mm Hg.…”
Section: Coffeementioning
confidence: 99%
“…10 As opposed to caffeine, CGA have been demonstrated to have antihypertensive effects, 11,12 possibly via nitric oxide-mediated vasodilation. 12 Results from an RCT of 23 healthy adults showed that CGA ingestion significantly reduced systolic blood pressure by 2.41 mm Hg and diastolic blood pressure by 1.53 mm Hg.…”
Section: Coffeementioning
confidence: 99%
“…32) Inhibition of Nox1 expression and activity by chlorogenic acid, one of the polyphenol components contained in coffee, has contributed to decrease free radical production related to hypertension. 33) Our previous results showed that, the polyphenol content of FBE exhibited antioxidative activity of IC50 at 100.37 mg/mL 10) providing protection against oxidative stress and suppression of ROS in SHRSP.…”
Section: Discussionmentioning
confidence: 99%